Positive health coaching: a conceptual analysis - Loughnane, Croía; Burke, Jolanta; Byrne, Elaine; Iglesias-Cans, Marina; Scott, Ciara; Collins, Mary; Bretherton, Roger; O’Donovan, Roisin; van Nieuwerburgh, Christian; Dunne, Pádraic J. (Frontiers in Psychology, 2025)
Positive health coaching (PHC) is a novel approach designed to address the growing need for a more holistic perspective on health to combat the rising epidemic of non-communicable diseases (NCD). Extending beyond disease prevention, PHC promotes complete physical, mental, and social wellbeing, aligning with the World Health Organisation (WHO) vision of health as a resource for everyday life. This paper introduces the conceptual analysis for PHC, which emerged from the wider theoretical base of Positive Health Sciences (PHS). PHC is an interdisciplinary field that integrates medical and psychological approaches to promote a dynamic and comprehensive orientation and journey toward positive health. PHC bridges the gap between theory and practice by integrating insights and strategies from lifestyle medicine, positive psychology, health psychology, and coaching psychology. While the first three elements establish the PHS foundation of PHC, the fourth component operationalizes these theories through coaching strategies. This paper aims to guide readers on a journey from understanding the foundational principles of PHS to exploring how PHC operationalizes these concepts to promote overall health and wellbeing.